Platelet‐rich plasma‐based bioactive membrane as a new advanced wound care tool. (18th April 2017) - Spanò, Raffaele; Muraglia, Anita; Todeschi, Maria R.; Nardini, Marta; Strada, Paolo; Cancedda, Ranieri; Mastrogiacomo, Maddalena
Abstract: Chronic skin ulcers, consequence of diabetes and other pathological conditions, heavily compromise the patient life quality and represent a high and constantly growing cost for National Health Services. Autologous platelet‐rich plasma (PRP), has been proposed to treat these lesions. The absence of guidelines for the PRP production and the need of a fresh preparation for each treatment lead us to develop a protocol for the production of an allogenic PRP‐based bioactive membrane (BAM), standardized for platelet concentration and growth factor release. This work compares BAMs obtained starting from two different platelet concentrations. There was no direct correlation between the amount of growth factors released by BAM in vitro and the initial platelet count. However, different release kinetics were noticed for different growth factors, suggesting that they were differently retained by the two BAMs. The angiogenic potential of both BAMs was determined by Luminex Angiogenesis Assay. The biological activity of the factors released by the two BAMs was confirmed by cell proliferation and migration. A diabetic mouse chronic ulcer model was used to define the best PRP therapeutic dose in vivo . Both BAMs induced wound healing by increasing the thickness of the regenerated epidermis and the vessel number. However, a too high platelet concentration resulted in a slowdown of the membrane resorption that interfered with the skin healing. Overall, the results indicate that the BAMs could represent a natural and effective wound healing tool for the treatment of skin ulcers. Copyright © 2016 John Wiley & Sons, Ltd.